2020
DOI: 10.48084/etasr.3549
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Hyperparameters on a Sentiment Analysis Model

Abstract: This paper focuses on the performance analysis of hyperparameters of the Sentiment Analysis (SA) model of a course evaluation dataset. The performance was analyzed regarding hyperparameters such as activation, optimization, and regularization. In this paper, the activation functions used were adam, adagrad, nadam, adamax, and hard_sigmoid, the optimization functions were softmax, softplus, sigmoid, and relu, and the dropout values were 0.1, 0.2, 0.3, and 0.4. The results indicate that parameters adam and softm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Sentiment analysis processes and identifies the data of certain domains through natural language processing. Sentiment analysis using social media plays a crucial role in various fields such as social development, people's awareness, economic development [10][11][12]. Indeed, many studies applied ML, and Deep Learning (DL) methods and algorithms to explore and investigate the public's sentiments on social media platforms towards the outbreak of COVID-19 and its emerging variants [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Sentiment analysis processes and identifies the data of certain domains through natural language processing. Sentiment analysis using social media plays a crucial role in various fields such as social development, people's awareness, economic development [10][11][12]. Indeed, many studies applied ML, and Deep Learning (DL) methods and algorithms to explore and investigate the public's sentiments on social media platforms towards the outbreak of COVID-19 and its emerging variants [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Table 8 shows papers that reported the sources of the datasets used for conducting experiments along with their corresponding categories and description. Here, the data were mostly collected by conducting surveys among students and teachers or by providing questioners to collect feedback from the students Education/research platforms [14,31,36,40,[44][45][46]48,58,61,70,78,82,84,86,93,95,99,101] This category contains the data extracted from online platforms providing different courses such as Coursera, edX, and research websites such as ResearchGate, LinkedIn, etc.…”
Section: Rq5 What Are the Most Common Sources Used To Collect Students' Feedback?mentioning
confidence: 99%
“…From the related reviewed articles, we observed that very few studies employed word embedding techniques to represent textual data collected from different sources. Only one article [48] employed the Word2Vec embedding model to learn the numeric representation and supply it as an input to the long short-term memory (LSTM) network. In addition to Word2Vec, GloVe and FastText models were used in two articles [14,45] to generate the embeddings for an input layer of CNN and compare the performance of the proposed aspect-based opinion mining system.…”
Section: Rq7 What Are the Most Common Data Representation Techniques Used For Sentiment Analysis?mentioning
confidence: 99%
“…Several studies utilized sentiment analysis in different ways. Multilingual student comments, obtained through student feedback, were used to evaluate online courses' effectiveness and teachers' performance in [3,[15][16][17]. In [3], the dataset was collected using approximately 4000 student comments through surveys conducted on 25 university courses to evaluate the performance of a professor who had been teaching for 10 years, while the sentiment analysis was directed including positive, negative, and eight more emotions.…”
Section: Related Workmentioning
confidence: 99%
“…The performance improved when using the softmax activation function, reaching 89%, 99%, and 90% during training, testing, and validation, respectively. Deep learning was applied on a course evaluation dataset with 3000 student comments using three predefined classes in [17], while the results showed that relu and softmax performed better.…”
Section: Related Workmentioning
confidence: 99%